Framing windows to the past comparative content and textual analyses of heritage reports in Manila Bulletin, Philippine Daily Inquirer and Philippine Star from 2011 to 2012 - Pascual, Ana Marie Angelica De Guzman (2013)
"This study aims to examine what the top three widely circulated broadsheets in the Philippines - Manila Bulletin, Philippine Daily Inquirer, and Philippine Star - have each done to contribute to bringing heritage issue into public consciousness. Using content analysis, all heritage features published by the three broadsheets from 2011 to 2012 were evaluated in terms of presence and emphasis, scope of coverage, and frames of focus. Features on sites that were covered by all three newspapers were further subjected to comparative textual analysis in order to gauge the accuracy and comprehensiveness of each paper's heritage reportage. In terms of presence and emphasis, scope of coverage, and comprehensiveness, within the time frame given, Inquirer did a better job covering heritage issues, compared to Star and Bulletin. Although Star was as comprehensive and accurate in its reportage as Inquirer, it did not give as much emphasis on heritage issues as the other two newspapers. On the other hand, although Bulletin did give sufficient emphasis on heritage issues, its features weren't as comprehensive as the features of the other two broadsheets. Heritage a a tourism commodity was the most used fram of focus among all three broadsheets."